Activity‐based costs of plasma transfusions in medical and surgical inpatients at a US hospital. Issue 1 (25th February 2016) - Shander, A.; Ozawa, S.; Hofmann, A.
Abstract : Background and objectives: Fresh frozen plasma (FFP) usage has significantly increased over the last decade leading to elevated healthcare costs. Although FFP is used in several clinical settings, it is often inappropriately transfused and evidence for its clinical efficacy is poor. Here, we describe plasma usage and transfusion costs in a real‐world US inpatient setting to determine the cost‐effectiveness of FFP transfusion and for comparison to various patient blood management (PBM) options to treat coagulopathies. Materials and methods: All activities related to plasma transfusion recorded at a single US hospital over one calendar year were collected in a stepwise manner using an activity‐based costing (ABC) methodology. This model maps all technical, administrative and clinical processes inherent to the cost of plasma. Results: Of 18 200 inpatients recorded, 849 were charged for blood products. In total, 136 medical and surgical inpatients were charged for 577 units of FFP, receiving a total of 534 units; 43 units were charged but not transfused. The total cost per unit of FFP transfused was $409·62 and $1, 608·37 per patient transfused with FFP. Wasted products, in‐hospital processes and overhead costs were found to account for 89·8% of the total cost of FFP transfusions. Conclusion: This study is the first to use ABC methodology to determine the full cost of plasma transfusion in a US inpatient setting. These data reveal the true cost of plasma, providing a useful reference point to compare with the cost of other PBM options to manage coagulation disorders.